Molecular phylogenetics, a new classification, and a new genus of the Neotropical fish family Anostomidae (Teleostei: Characiformes) - Sidlauskas, Brian L.; Melo, Bruno F.; Birindelli, Jose L. O.; Burns, Michael D.; Frable, Benjamin W.; Hoekzema, Kendra; Dillman, Casey B.; Sabaj, Mark H.; Oliveira, Claudio [UNESP] (Soc Brasileira Ictiologia, 2025)
Phylogenetic reconstruction of the Neotropical freshwater fish family Anostomidae using multilocus sequence data from 97 species supports the recognition of three subfamilies: Leporellinae with one genus, Anostominae with six genera, and Leporininae with nine genera. We reassign many Leporinus species to a redefined Hypomasticus and allocate Leporinus striatus to a new monotypic genus sister to Abramites and Megaleporinus. These taxonomic changes clarify that section of the anostomid tree and partially solve the longstanding non-monophyly of Leporinus. Though many relationships inferred herein match earlier morphological hypotheses, the subfamily Anostominae appears as the unambiguous sister to Leporellus, not Laemolyta, indicating that the superior mouths of Anostominae and Laemolyta evolved convergently. Several other clades have converged on subterminal or inferior mouths, including lineages within Hypomasticus, Leporellus, Leporinus, and Schizodon. This largest-ever phylogeny for Anostomidae will support further taxonomic research and provide a scaffold for morphological, biogeographic, and evolutionary studies in this transcontinental group of Neotropical fishes.
Keywords: Characoidei; Headstanders; Leporinus; Ostariophysi; South America